A cross-sectional comparative study of anxiety and depression among doctors working in covid care centres during the first and second waves of COVID-19 pandemic in Chennai, Tamil Nadu - Rajaraman Nivetha,; Arumugam , Balaji; Annamalai Radhakrishnan,; Vikram Ashokkumar,; Arunagirinathan Keerthana, (Asian Journal of Medical Sciences, 2023)
Background: Doctors are at significant risk of developing psychological morbidity during the coronavirus diseases 2019 (COVID-19) Pandemic due to the shortage of resources and changing medical protocols. The fear, stigma, prejudice, and marginalization toward COVID-19 added with the physical discomfort of using personal protective equipment kits leads to mental exhaustion among doctors. Aims and Objectives: The aim of the study was to estimate and compare the prevalence and level of anxiety and depression along with its risk factors among doctors working in COVID Care centers during the COVID-19 pandemic’s First and Second wave. Materials and Methods: A cross-sectional study among 200 doctors working in the COVID care centers using mailed questionnaires was conducted. A convenient sampling method was used to include the study participants. Collected data were entered in an MS Excel spreadsheet and analyzed using SPSS version 21.0. Results: During the first wave of the COVID-19 pandemic, the observed prevalence of the symptoms of depression and anxiety respectively among doctors was 42% and 56% whereas it increased to 83% and 82%, respectively, during the second wave. Conclusion: The present study highlighted the high prevalence of anxiety and depression among doctors. As the COVID-19 pandemic continues to sweep the world, the global doctors’ community have to be sensitized to the prevalence of psychological disorders and a necessary appropriate psychological support strategy needs to be developed.